Influence of expectation and campus racial climate on undergraduates' interracial interaction - Tamam, Ezhar; Idris, Fazilah; Yee, Wendy Mei Tien; Ahmad, Mona Alkauthar (Routledge, 2013)
In this study, the authors examine the influence of interracial interaction expectation and campus racial climate perception on attitudes toward interracial interaction which, in turn, influences the levels of interracial interaction among students at a multicultural university in Malaysia. Interaction across race is fundamental to students' growth and development. Responses from 193 Malay and 165 Chinese students were analysed by means of hierarchical regression. Results support the hypothesized influence of interracial interaction expectation and campus racial climate perception on attitudes toward interracial interaction for the Chinese students. For the Malay students, however, only interracial interaction expectation is significant. Attitudes toward interracial interaction, in turn, significantly predict levels of interracial interaction for both groups. The results support the hypothesized differential strength of relationships among the variables for the two racial groups. Implications for higher education are discussed.